Make or wreck vegetations in heritage architectural ruins - Malaga, Juanito M. (Espasyo : Journal of Philippine Architecture and Allied Arts, 2012)
The Spanish colonization of the Philippines a few centuries ago gave the country countless architectural treasures such as civic buildings, churches, visitas, cemeteries, capillas, bridges and mojones. Although some of these structures are in good condition, a number needs urgent repair and most are in a state of ruins. This paper looks into the cases of two notable Heritage Architectural Ruins (HAR) in Albay, the Cagsawa and the Sinimbahanan, to determine the context of vegetation outgrowth relative to its destructive and beneficial aspects. It attempts to formulate a framework that would aid in weighing the positive and negative effects of vegetation in ruins. The paper argues that a strategic scheme in determining these effects could help in the preservation of heritage architectural treasures, thereby highlighting their significance and making them more enduring.